Impact of myocardial infarction on intraventricular vortex and flow energetics assessed using computational simulations. (25th April 2019) - Chan, Bee Ting; Ahmad Bakir, Azam; Al Abed, Amr; Dokos, Socrates; Leong, Chin Neng; Ooi, Ean Hin; Lim, Renly; Lim, Einly
Abstract: Flow energetics have been proposed as early indicators of progressive left ventricular (LV) functional impairment in patients with myocardial infarction (MI), but its correlation with individual MI parameters has not been fully explored. Using electro–fluid‐structure interaction LV models, this study investigated the correlation between four MI parameters: infarct size, infarct multiplicity, regional enhancement of contractility at the viable myocardium area (RECVM), and LV mechanical dyssynchrony (LVMD) with intraventricular vortex and flow energetics. In LV with small infarcts, our results showed that infarct appearance amplified the energy dissipation index (DI), where substantial viscous energy loss was observed in areas with high flow velocity and near the infarct‐vortex interface. The LV with small multiple infarcts and RECVM showed remarkable DI increment during systole and diastole. In correlation analysis, the systolic kinetic energy fluctuation index (E′) was positively related to ejection fraction (EF) ( R 2 = 0.982) but negatively correlated with diastolic E′ ( R 2 = 0.970). Diastolic E′ was inversely correlated with vortex kinetic energy ( R 2 = 0.960) and vortex depth ( R 2 = 0.876). We showed an excessive systolic DI could differentiate infarcted LV with normal EF from healthy LV. Strong flow acceleration, LVMD, and vortex‐infarct interactions were predominant factors that induced excessive DI in infarcted LVs. Instead of causing undesired flow turbulence, high systolic E′ suggested the existence of energetic flow acceleration, while high diastolic E′ implied an inefficient diastolic filling. Thus, systolic E′ is not a suitable early indicator for progressive LV dysfunction in MI patients, while diastolic E′ may be a useful index to indicate diastolic impairment in these patients. Abstract : Our computational study showed that infarct appearance amplified the energy dissipation index (DI), where substantial viscous energy loss was observed in areas with high flow velocity and near the infarct‐vortex interface. Strong flow acceleration, left ventricular mechanical dyssynchrony (LVMD), and vortex‐infarct interactions were predominant factors that induced excessive DI in infarcted left ventricles (LVs). Instead of causing an undesired flow turbulence, high systolic kinetic energy fluctuation index (E′) suggested the existence of an energetic flow acceleration, while high diastolic E′ implied an impaired diastolic filling.